The Influence of Influencer Marketing and Marketplace Platforms on Online Fashion Buying Interest in Generation Z Through Consumer Motivation - Andi Reski Nurhikmah; Nurliana Nurliana (Journal of Entrepreneur, Business and Management, 2026)
Fashion is a form of self-expression that reflects a person's identity, lifestyle, and social status. In addition to being a basic need, fashion is also a means  of visual  communication that allows individuals to express their personality, aesthetic preferences, and cultural affiliations. Along with the development of technology, especially through online platforms and social media, fashion is also increasingly accessible to various groups, including the younger generation (generation z), who are heavily influenced by influencers and digital trends. Therefore, fashion is now not only related to the aspect of style, but also to the ever-evolving social, cultural, and economic dynamics. One way to understand the behavioral dynamics of the younger generation in the fashion  industry is to look at the role of digital marketing, especially through influencer marketing and marketplace platforms. This study aims to determine the direct and indirect influence of influencer marketing, marketplace platforms, and consumer motivation on online fashion buying interest. This study uses a quantitative approach of the Descriptive Explanatory  type which describes the relationship between variables with a population of 114 Generation Z. Sampling technique using Proportional Random Sampling amounted to 80 students of generation z. The results of the study showed that directly and indirectly influencer marketing, marketplace platforms, consumer motivationhas a significant effect on the interest in buying fashion online. Based on the research that has been conducted, it is expected to enrich the understanding of Generation Z's digital consumer behavior and contribute to the development of marketing strategies that are more relevant and impactful for  the online fashion  industry as well as provide practical benefits for marketers and brands in developing the right marketing strategy.